Fortifications, habitats et peuplement entre Bougie et la Qal ͑a des Banū Ḥammād - Mohamed Meouak (Mélanges de la Casa de Velázquez, 2006)
This article proposes an updating of information available on historical geography, tribal society and the manifestations of the various levels of power in the Petite Kabylie in the Middle Ages, building upon an account of a journey left by al-Idrīsī, an Arab geographer of the 6th/12th century. Based additionally on a thorough sifting of Arab sources for the mediaeval Maghrib and of the modern literature, this article explores the areas of research dealing with fortifications, habitats and modes of settlement. Starting from examples of land use and settlement from late Antiquity, in some cases contrasting autochthonous social structures (tribes, mountain settlements, etc.) with Roman concepts of land development, we conclude, among other things, that an examination of such issues can only produce satisfactory results if archaeological methods and the specific characteristics of the Maghrib are systematically taken into account.